Prevalência das doenças de equinos no Rio Grande do Sul - Pierezan, Felipe (2009)
The necropsy reports of 335 horses necropsied at the LPV-UFSM between 1968-2007 were reviewed in order to determine the necropsy findings related with cause of death or reason for euthanasia. The distribution of these findings by organ system were as follows: digestive (79/335 [23.6%]), striated muscle and skeleton (47/335 [14.0%]), nervous (37/335 [11.0%]), respiratory (35/335 [10.4%]), integument (31/335 [9.3%]), hematopoietic (24/335 [7.2%]), cardiovascular (13/335 [3.9%]), reproductive (12/335 [3.5%]), urinary (7/335 [2.1%]), and endocrine (3/335 [0.9%]). The cause of death was not possible to be determined in 47 (14.0%) necropsied horses. Displacements of the intestines (17/79 [21.5%]) were the main findings in digestive system, followed by obstruction and impactation (14/79 [17.7%]). Torsion were the type of displacement more frequently observed in the intestines (14/17 [82.4%]). Among those the more prevalent affected the small intestine (7/14 [50%]). Most horses dying from fractured bones were 1-5-year-old. The most prevalent diseases in the nervous system were leukoencephalomalacia and trypanosomiasis, whereas respiratory depression due to anesthesia was the leading cause of death related to the respiratory system. Equine infectious anemia was the most diagnosed infectious disease and the main reason leading to euthanasia.